2011
DOI: 10.1128/mbio.00078-11
|View full text |Cite
|
Sign up to set email alerts
|

Prion Disease Blood Test Using Immunoprecipitation and Improved Quaking-Induced Conversion

Abstract: A key challenge in managing transmissible spongiform encephalopathies (TSEs) or prion diseases in medicine, agriculture, and wildlife biology is the development of practical tests for prions that are at or below infectious levels. Of particular interest are tests capable of detecting prions in blood components such as plasma, but blood typically has extremely low prion concentrations and contains inhibitors of the most sensitive prion tests. One of the latter tests is quaking-induced conversion (QuIC), which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 45 publications
7
158
0
2
Order By: Relevance
“…can reliably identify preclinical cases to minimize the risk of iatrogenic disease transmission via blood-derived products. Experimental detection of PrP TSE in animal cerebrospinal fluid (CSF) (29), whole blood (21,22), plasma (27)(28)(29)(30)71), buffy coat (24 -26), and urine (74) and in human CSF (12,75), whole blood (6 -8), and urine (76,77) has been achieved by different methods that rely on the concentration or amplification techniques to bring PrP TSE levels to the detection threshold of biochemical assays. Although the presence of PrP TSE in blood exosomes has been suggested previously (48), biochemical detection has been complicated by the low levels of PrP TSE in blood and the concomitantly large volumes required for exosome isolation by standard methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…can reliably identify preclinical cases to minimize the risk of iatrogenic disease transmission via blood-derived products. Experimental detection of PrP TSE in animal cerebrospinal fluid (CSF) (29), whole blood (21,22), plasma (27)(28)(29)(30)71), buffy coat (24 -26), and urine (74) and in human CSF (12,75), whole blood (6 -8), and urine (76,77) has been achieved by different methods that rely on the concentration or amplification techniques to bring PrP TSE levels to the detection threshold of biochemical assays. Although the presence of PrP TSE in blood exosomes has been suggested previously (48), biochemical detection has been complicated by the low levels of PrP TSE in blood and the concomitantly large volumes required for exosome isolation by standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…PrP TSE has been successfully detected in the following: in whole blood of experimentally infected mice and hamsters, in sheep with natural scrapie and experimental BSE, and in white-tailed deer afflicted with CWD (21)(22)(23); in buffy coats of hamsters and sheep experimentally infected with scrapie (24 -26), as well as in plasma of mice and hamsters with scrapie; and in sheep and white-tailed deer naturally and experimentally infected with scrapie and CWD, respectively (27)(28)(29)(30). However, it is still not fully understood in what blood component TSE infectivity and/or PrP TSE reside and whether and how blood contributes to the spread of the disease from the periphery to the brain.…”
mentioning
confidence: 99%
“…It is thought that this may be due to condition-dependent factors, such as differences in the propensity to form an amyloidogenic precursor, or an intermediate that may be totally different from the native rPrP C that interacts more favourably and efficiently with prion seeds. Alternatively, it may be due to the occurrence of off-pathway changes that may promote spontaneous, prion-independent fibril formation (false positives) or remove rPrP C from the assembly component pool (Orrú et al, 2011).…”
Section: Real-time Quaking-induced Conversion (Rt-quic)mentioning
confidence: 99%
“…Other researchers have attempted a modified PMCA approach, known as enhanced quaking-induced conversion (e-QuIC) (Orrú et al, 2011). This approach combines QuIC, which can be as sensitive as an in vivo bioassay and in which prions induce the polymerization of recombinant PrP C (rPrP C ) into amyloid fibrils by applying cycles of shaking and rest (Atarashi et al, 2008;Orrú et al, 2009), with specific IP of PrP Sc using the 15B3 antibody (Korth et al, 1997;Biasini et al, 2008Biasini et al, , 2009.…”
Section: Real-time Quaking-induced Conversion (Rt-quic)mentioning
confidence: 99%
“…However, ongoing validation studies have demonstrated that the outcomes of RT-QuIC reactions depend on the exact conditions employed (biochemical, chemical and physical), as well as the nature of the sample and recombinant substrate. The protocol under evaluation by the National Microbiology Laboratory has been tested extensively for the detection of sporadic CJD (10,11,15,16 ). Using this protocol the Prion Laboratory Section achieved 100% sensitivity and 100% specificity in the evaluation of an external sporadic CJD infected CSF proficiency panel.…”
Section: Summary Of Test Resultsmentioning
confidence: 99%